(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Non-alcoholic fatty liver disease (NAFLD) is considered as a common cause of chronic liver disease. It is potentially progressive towards non-alcoholic steatohepatitis (NASH), hepatic fibrosis, cirrhosis and its complications including hepatocellular carcinoma (HCC). So, the need for predictive factors of NAFLD is important. Among the different serum markers in NAFLD, serum uric acid (SUA) has emerged as a possible predictor of severity of liver damage. This observational cross sectional study was carried out involving 100 patients from the department of gastroenterology, BSMMU, Dhaka, with the intention to determine the association of serum uric acid (SUA) level with non-alcoholic fatty liver disease. Among them, 55 were having NAFLD; and 45 subjects without NAFLD were considered as control. The diagnosis of NAFLD was based on the guidelines for the assessment and management of NAFLD in the Asia-pacific region. Serum uric acid, liver enzymes, glycaemic status, serum lipid profile and anthropometric measurements were compared between NAFLD group & control. The mean age was found 41.34 + 10.88 years in both the groups. Male were 62% & female were 38% among the study population. Forty percent of the study subjects were overweight, 23% were obese and 37% had normal body weight. NAFLD patients had significantly higher serum uric level (6.9 + 0.89 mg/dl) in comparison to non-NAFLD group (4.3 +0.87 mg/dl). The study showed that serum uric acid level was significantly associated with NAFLD. Serum uric acid may be used as a useful additional marker to assess the risk of development of NAFLD in the clinical setting of metabolic syndrome. BSMMU J 2021; 14(4): 125-131